Going to a stadium - Rissman, Rebecca (Chicago Heinemann Library, 2012)
Looks at sports stadiums, including tennis courts, baseball parks, and race tracks
World around us
a gift from book africa
1 2 13
Keywords: School field trips; Stadiums -- Juvenile literature